2003
DOI: 10.1615/critreveukaryotgeneexpr.v13.i24.120
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Receptor and Insulin-like Growth Factor-I Immunoreactivity in Osteoclast-like Cells During Tooth Eruption in the Toothless (Osteopetrotic) Rat Following Treatment with Colony-Stimulating Factor-1

Abstract: ABSTRACT:In the toothless (tl/tl) osteopetrotic rat, teeth form but fail to erupt. Treatment of tl/tl rats with colony-stimulating factor-1 (CSF-1) activates bone resorption by osteoclasts, permits tooth eruption, and upregulates the immunoreactivity of bone marrow mononuclear cells to growth hormone receptor (GHr) and insulinlike growth factor (IGF)-I. This study examined the distribution of tartrate-resistant acid phosphatase (TRAP) and immunoreactivity for GHr and IGF-I in osteoclast-like cells located on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Unsurprisingly, 36 genes involved in the differentiation, maturation, and function of myeloid-lineage cells showed increased expression in the 33-dpi MHV-infected spinal cord (Table 2, Figure 2, Tables S2 and S3). These genes are involved in scavenging (CD68, MSR1), signaling (Ms4a7, Tyrobp, TREM2, Gp49a, and AIM [61][62][63][64][65][66]), pathogen destruction (Lgals3 [67]), and monocyte differentiation (Tyrobp, TREM2, Mpeg1, and gpnmb [68][69][70][71][72][73]). Two of the genes for which expression was most highly induced during MHV persistence were TREM2 (Triggering receptor expressed on myeloid cells 2) and DAP12 (DNAX-activating protein of 12kDa), both of which are involved in myeloid differentiation and function ( Table 2).…”
Section: Increased Expression Of Genes With Roles In Osteoclast Develmentioning
confidence: 99%
“…Unsurprisingly, 36 genes involved in the differentiation, maturation, and function of myeloid-lineage cells showed increased expression in the 33-dpi MHV-infected spinal cord (Table 2, Figure 2, Tables S2 and S3). These genes are involved in scavenging (CD68, MSR1), signaling (Ms4a7, Tyrobp, TREM2, Gp49a, and AIM [61][62][63][64][65][66]), pathogen destruction (Lgals3 [67]), and monocyte differentiation (Tyrobp, TREM2, Mpeg1, and gpnmb [68][69][70][71][72][73]). Two of the genes for which expression was most highly induced during MHV persistence were TREM2 (Triggering receptor expressed on myeloid cells 2) and DAP12 (DNAX-activating protein of 12kDa), both of which are involved in myeloid differentiation and function ( Table 2).…”
Section: Increased Expression Of Genes With Roles In Osteoclast Develmentioning
confidence: 99%
“…GH and IGF-1 facilitate bone resorption by stimulating the pre-existing OCs. In contrast to some OCs like cell types, the blockade of IGF-1 abolishes the effect of GH on OCs entirely 91 . CBL-B mediates Insulin receptor substrate degradation and confers the IGF-1 resistance to OCs.…”
Section: The Role Of E3 Ubiquitin Ligases In Bone Resorptionmentioning
confidence: 88%
“…Similarly, treatment of normal women with IGF‐I activates osteoclasts and increases bone resorption 41. In vitro , it has been demonstrated that both GH and IGF‐I can each act through direct actions to stimulate osteoclast differentiation (osteoclasts and precursors express both GH and IGF‐I receptors 43, 44), and also through indirect and osteoprotegerin‐ and/or receptor activated nuclear factor κB ligand‐dependent actions to enhance osteoclast maturation and bone resorption activity of mature osteoclasts, possibly via stromal cells, including osteoblasts 36, 37, 42, 45, 46.…”
Section: Discussionmentioning
confidence: 99%